The theoretical understanding of risk perception and dual-method contraceptive decision-making among Texas adolescent and young adult cisgender females - Lauren Holt; Amy Corneli; Eleanor Stevenson; Jonas J. Swartz; Michael V. Relf (PLoS ONE, 2026)
In this paper we use a constructivist grounded theory approach to conduct individual, qualitative interviews with a racially and ethnically diverse group of adolescent and young adult cisgender females (AYACF) (18–24 years of age) to generate theoretical knowledge of the relationship between Social Determinants of Health (SDOH), STI and HIV risk perception, and dual-method contraceptive decision-making (the use of, both, a prescribed contraceptive [commonly referred to as “birth control”] and a condom during vaginal intercourse). Twenty-five AYACF were selected through theoretical sampling. Data were collected using semi-structured interviews and analyzed using constant comparison. AYACF expressed having a greater fear of pregnancy than sexually transmitted infections (STIs). They described deferring to their partners and making assumptions about their partner’s STI status based on partner and relationship factors, therefore not needing to engage in condom negotiation. Mother-daughter sexual health conversations and state school-based sex education and abortion policies influenced participants’ STI risk perception and dual-method contraceptive decision-making. Participants who were diagnosed with an STI reported experiencing a shift in perception about their likelihood of acquiring an STI, often resulting in behavior change. These findings are important as they provide insight into the complex decision-making processes, influenced by SDOH, that a racially and ethnically diverse group of AYACF associate with STI risk perception and dual-method contraceptive use.